JOB SATISFACTION: A BIBLIOMETRIC ANALYSIS - Prilatama, Aris; Churiyah, Madziatul (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
This study aims to conduct a bibliometric analysis of co-authorship, co-occurrence, and citation related to job satisfaction. The method used in this study involves selecting the keyword "job satisfaction" from ScienceDirect.com, resulting in a total of 30,839 filter records within the range of 2000-2023. After verification, 83 articles that met the criteria were obtained using VosViewer Journal application. The results revealed 70 clusters with the strongest link strength and total link, as well as keywords that are directly related to job satisfaction such as well-being, diversity, COVID-19, autonomy, stress, job fatigue, polynomial regression, and performance. The implications of this study are that it provides valuable insights into the factors and issues that affect job satisfaction, and these findings can be used to inform policies and practices that promote job satisfaction among employees.